Decreasing blood wastage during ex vivo lung perfusion recovery through utilization of thermal control technology. Issue 12 (9th November 2022) - Johnson, Blaine; Bucio, Jamie; Salerno, Christopher; Jeevanandam, Valluvan; Song, Tae; Wool, Geoffrey
Abstract: Background: The Organ Care System (OCS) is a revolutionary ex vivo organ perfusion technology that can potentially expand the organ retrieval range. The OCS Lung device uses packed red blood cells (pRBC) with a proprietary solution. We report the ability to reduce blood waste during this procedure by using a thermal packaging solution in conjunction with the OCS platform. Methods: We retrospectively reviewed all OCS Lung recoveries performed by our recovery team, using pRBCfrom May 2019 to January 2021. Initially, units were stored using passive refrigeration with the Performance cooler at a temperature range of 1–6°C for 4 h. Subsequently, thermal control technology with the ProMed cooler was utilized to maintain the same temperature range for 72 h. Results: Twenty‐three recoveries were initiated with 63 pRBC. The Performance cooler was used for 8, while the ProMed cooler for 13. 37.5% of pRBC transported with the Performance cooler was used within the validated time range, while 25.0% were used beyond the validated time range based on clinical judgment. In addition, 37.5% of pRBC transported with the Performance cooler were returned to the institution after canceled recoveries with an estimated loss of 1800; the ProMed cooler had no wastage. Conclusions: This study showed that using an advanced thermal packaging solution facilitates proper storage of pRBC and represents an advancement for extended donor lung preservation. The elimination of blood wastage in this initial study portends ongoing benefits for the limited blood supply and reduced cost.